The Influence of Current Ratio and Return on Assets on Share Prices of Companies in the Banking Sector Listed on the Indonesia Stock Exchange for the Period 2020–2024. - Afendi, Afendi; Samryn, L. M. (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the effect of current ratio and return on assets on stock prices in banking sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. The data used in this study is secondary data. The research sample consists of 28 banking sector companies listed on the Indonesia Stock Exchange, selected using purposive sampling. The method used is quantitative. The data were analyzed using statistical analysis and simple linear regression analysis as well as multiple linear regression analysis using SPSS 30. Hypothesis testing was performed using the t-test and f-test. Based on the t-test, it shows that the current ratio has a positive but insignificant effect on stock prices, while return on assets has a significant effect on stock prices. Based on the F test, the current ratio and return on assets variables have an effect on stock prices but are not significant